Two-dimensional material dispersion liquid as well as preparation method and application thereof

By using super acid with a Hamit acidity less than -1 as a dispersant, efficiently dispersing and processing two-dimensional materials, the existing problems of poor dispersion effect and low processing efficiency are solved, and high concentration dispersion and multiple composite materials are achieved. preparation.

CN119118201APending Publication Date: 2024-12-13TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411253000.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing solvents have poor effects when dispersing two-dimensional materials, cannot achieve high concentration dispersion and effective processing, and have low processing efficiency, so they cannot be directly used to prepare composites.

Method used

Use super acids with a Hamit acidity of less than -1, such as trifluoromethylsulfonic acid, fume sulfuric acid, chlorosulfonic acid or methanesulfonic acid as dispersants, and prepare them through mixing and shearing and peeling with two-dimensional materials. High concentration of two-dimensional material dispersions are produced and used to prepare composite fibers, microspheres, films and colloids.

Benefits of technology

It realizes high concentration stable dispersion and efficient processing of two-dimensional materials, improves peeling efficiency and throughput, and can be directly used for the preparation of multiple composite materials, solving the problems of single solvent functionality and low processing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118201A_ABST
    Figure CN119118201A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional material dispersion liquid and a preparation method and application thereof, the two-dimensional material dispersion liquid comprises a two-dimensional material and a dispersing agent, and the dispersing agent is superacid with Hammett acidity less than-1. The two-dimensional dispersion liquid provided by the invention has the characteristic of high-concentration dispersion. In addition, the two-dimensional material dispersion liquid can be used for preparing compound fibers, compound microspheres, compound films and colloids, and processing diversification of the two-dimensional material dispersion liquid is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of two-dimensional materials, and in particular to a two-dimensional material dispersion, a preparation method thereof, and applications thereof. Background Art

[0002] The dispersion of two-dimensional materials is an important prerequisite for their effective processing. Conventional solvents have poor dispersion effects and single functionality, making it difficult to achieve effective further processing and cannot be directly used to process them into two-dimensional material composites. Summary of the invention

[0003] In view of this, the present application provides a two-dimensional material dispersion, a preparation method and application thereof that can solve the above-mentioned technical problems.

[0004] A two-dimensional material dispersion, comprising:

[0005] A two-dimensional material and a dispersant, wherein the dispersant is a superacid with a Hammett acidity of less than -1.

[0006] Furthermore, the dispersant includes at least one of trifluoromethanesulfonic acid, oleum, chlorosulfonic acid, methanesulfonic acid or fluorosulfonic acid.

[0007] Furthermore, the two-dimensional material includes one or more of hexagonal boron nitride, graphene, molybdenum disulfide or tungsten disulfide.

[0008] Furthermore, the concentration of the two-dimensional material in the two-dimensional material dispersion is 1 mg / mL to 200 mg / mL.

[0009] The present invention also provides a method for preparing the above-mentioned two-dimensional material dispersion, comprising the following steps:

[0010] Providing a dispersant, wherein the dispersant is a superacid having a Hammett acidity of less than -1;

[0011] The two-dimensional material and the dispersant are mixed, sheared and peeled to obtain a two-dimensional material dispersion.

[0012] Furthermore, the shearing rotation speed is 7000 rpm to 30000 rpm, and the shearing time is 1 h to 4 h.

[0013] The present invention also provides application of the two-dimensional material dispersion in preparing composite fibers.

[0014] The present invention also provides application of the two-dimensional material dispersion in preparing composite microspheres.

[0015] The present invention also provides application of the two-dimensional material dispersion in preparing a composite film.

[0016] The present invention also provides the use of the two-dimensional material dispersion in preparing a colloid.

[0017] Compared with the prior art, the dispersant used in this application can stably disperse various types of two-dimensional materials at extremely high concentrations, and can achieve further effective processing of the two-dimensional material dispersion. This application solves the problem that conventional solvents have a single functionality and cannot be directly used to process two-dimensional material composites. In addition, the preparation method provided in this application also has the characteristics of high stripping efficiency and high throughput. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1A This is a scanning electron microscope image of hexagonal boron nitride before shearing in Example 1 of the present application. Figure 1B This is a scanning electron microscope image of hexagonal boron nitride in the hexagonal boron nitride dispersion prepared in Example 1 of the present application.

[0019] Figure 2A This is a transmission electron microscope image of the graphene dispersion in Example 2 of the present application, Figure 2B This is a transmission electron micrograph of the molybdenum disulfide dispersion in Example 3 of the present application.

[0020] Figure 3 This is a physical picture of the hexagonal boron nitride dispersion with a concentration of 100 mg / mL prepared in Example 1 of the present application.

[0021] Figure 4 This is a physical picture of the hexagonal boron nitride dispersed colloid prepared in Example 9 of the present application.

[0022] Figure 5 The composite fiber of the two-dimensional material and Kevlar fiber prepared in Examples 11-13 of the present application, Figure 5 From left to right in the figure are graphene composite fibers, molybdenum disulfide composite fibers, and hexagonal boron nitride composite fibers.

[0023] Figure 6 This is a physical picture of the composite microspheres prepared using hexagonal boron nitride dispersion and Kevlar fiber in Example 16 of the present application.

[0024] Figure 7 The composite of the two-dimensional material and Kevlar fiber prepared in Examples 17-19 of the present application, Figure 7 From left to right in the figure are graphene composite film, boron nitride composite film, and molybdenum disulfide composite film. DETAILED DESCRIPTION

[0025] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.

[0026] Two-dimensional materials refer to materials in which electrons can only move freely (planar motion) in two dimensions at a non-nanoscale. Because their carrier migration and heat diffusion are confined within a two-dimensional plane, two-dimensional materials exhibit many unique properties. Their adjustable band gap properties are widely used in field effect transistors, optoelectronic devices, thermoelectric devices, and other fields; the controllability of their spin and valley degrees of freedom has attracted in-depth research in the fields of spin electronics and valley electronics; different two-dimensional materials have different anisotropies of electrical or optical properties due to the special properties of their crystal structures, including anisotropy of Raman spectra, photoluminescence spectra, second-order harmonic spectra, optical absorption spectra, thermal conductivity, electrical conductivity, and other properties, and have great development potential in the fields of polarized optoelectronic devices, polarized thermoelectric devices, bionic devices, polarized light detection, and other fields.

[0027] As an emerging type of material, two-dimensional materials have shown various excellent properties due to their special conformation and are currently one of the important areas of research and application for many scholars. The dispersion of two-dimensional materials is very necessary for their processing, but conventional solvents can only disperse them at low concentrations, and a large amount of reagents are used during the processing, resulting in environmental pollution and very limited processing efficiency. Therefore, how to choose a suitable liquid phase carrier to achieve high-concentration dispersion of two-dimensional materials and efficient processing and application is an important issue that needs to be solved urgently.

[0028] In view of this, the present application provides a two-dimensional material dispersion capable of high concentration dispersion, high stripping efficiency, high throughput and a variety of processing methods to address the shortcomings of the prior art.

[0029] The present application provides a two-dimensional material dispersion, comprising:

[0030] A two-dimensional material and a dispersant, wherein the dispersant is a superacid with a Hammett acidity of less than -1.

[0031] Hammett acidity is an indicator used to indicate the acidity of high concentration acid, and its value is obtained from the Hammett acidity function formula.

[0032] In some embodiments, the dispersant includes at least one of trifluoromethanesulfonic acid, oleum, chlorosulfonic acid, methanesulfonic acid or fluorosulfonic acid, wherein the Hammett acidity of trifluoromethanesulfonic acid is -14.6, the Hammett acidity of oleum is -12.0, the Hammett acidity of chlorosulfonic acid is -12.8, the Hammett acidity of methanesulfonic acid is -1.9, and the Hammett acidity of fluorosulfonic acid is -15.6.

[0033] In some embodiments, the two-dimensional material includes one or more of hexagonal boron nitride, graphite, graphene, molybdenum disulfide, or tungsten disulfide.

[0034] In some embodiments, the concentration of the two-dimensional material in the two-dimensional material dispersion is 1 mg / mL to 200 mg / mL, for example, 1 mg / mL, 10 mg / mL, 25 mg / mL, 50 mg / mL, 75 mg / mL, 100 mg / mL, 125 mg / mL, 150 mg / mL, 175 mg / mL, 200 mg / mL or within a range consisting of any two of the above values.

[0035] The present invention also provides a method for preparing the above-mentioned two-dimensional material dispersion, comprising the following steps:

[0036] Providing a dispersant, wherein the dispersant is a superacid having a Hammett acidity of less than -1;

[0037] The two-dimensional material and the dispersant are mixed, sheared and peeled to obtain a two-dimensional material dispersion.

[0038] The present application has no limitation on the particle size of the two-dimensional material. In some embodiments, the two-dimensional material can be ball-milled in advance and its size can be crushed to obtain a two-dimensional material powder with a smaller particle size.

[0039] In some embodiments, the shearing speed is 7000 rpm to 30000 rpm, and the shearing time is 1 h to 4 h. For example, the shearing speed is 7000 rpm, 10000 rpm, 15000 rpm, 20000 rpm, 25000 rpm, 30000 rpm, or within the range consisting of any two of the above values, and the shearing time is 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, or within the range consisting of any two of the above values.

[0040] The present invention also provides application of the two-dimensional material dispersion in preparing composite fibers.

[0041] In some embodiments, the two-dimensional material dispersion is mixed with a polymer to obtain a composite stock solution, and the composite stock solution is used to prepare composite fibers. The polymer includes but is not limited to nylon, polyetheretherketone or para-aramid fiber (Kevlar fiber). The concentration of the polymer in the composite stock solution can be 1 mg / mL to 200 mg / mL, and the proportion of the polymer in the composite stock solution can be 1 wt% to 99 wt%.

[0042] In some embodiments, the method for preparing composite fibers can be wet spinning, that is, a spinning solution formed by dissolving a high molecular polymer in a two-dimensional material dispersion is ejected through a spinneret into a fine stream and enters a coagulation bath to form fibers, wherein the coagulation bath includes but is not limited to deionized water, ethanol or dimethyl sulfoxide.

[0043] The present invention also provides application of the two-dimensional material dispersion in preparing composite microspheres.

[0044] In some embodiments, the two-dimensional material dispersion is mixed with a high molecular polymer to prepare composite microspheres. The obtained composite microspheres need to be placed on a silicon wafer with a temperature higher than the boiling point of the coagulation bath for drying. For example, if deionized water is selected as the coagulation bath, the obtained composite microspheres need to be dried on a silicon wafer at a temperature higher than 100° C., and then further dried in a vacuum drying oven at 65° C. or other drying equipment.

[0045] The present invention also provides application of the two-dimensional material dispersion in preparing a composite film.

[0046] In some embodiments, the two-dimensional material dispersion is mixed with a high molecular polymer and heated to form a colloid at a temperature of 80 to 100° C., cured with deionized water, and then scraped onto a scraping substrate to form a composite film.

[0047] In some embodiments, the scraping substrate includes, but is not limited to, a tetrafluoroethylene film or a stainless steel film.

[0048] The present invention also provides the use of the two-dimensional material dispersion in preparing a colloid.

[0049] In some embodiments, a solid salt for adjusting viscosity is added to the two-dimensional material dispersion so that the two-dimensional material dispersion forms a colloid, and the solid salt includes but is not limited to sodium chloride, lithium chloride or sodium fluoride.

[0050] The present application is described in detail below through specific embodiments.

[0051] Example 1

[0052] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0053] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0054] Example 2

[0055] Provide flake graphite with a particle size of 20μm to 30μm, dry it for use.

[0056] Add 1 g of the above-mentioned flake graphite to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake it thoroughly to make the flake graphite evenly dispersed. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours. The flake graphite is peeled off to become graphene, thereby obtaining a graphene dispersion with a graphene concentration of 100 mg / mL.

[0057] Example 3

[0058] Molybdenum disulfide with a particle size of 10 μm is provided and dried for later use.

[0059] Add 1 g of the above molybdenum disulfide to a reagent bottle containing 10 mL of trifluoromethylsulfonic acid, and shake thoroughly to evenly disperse the molybdenum disulfide powder. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a molybdenum disulfide dispersion with a molybdenum disulfide concentration of 100 mg / mL.

[0060] Example 4

[0061] Tungsten disulfide with a particle size of 2 μm is provided and dried for later use.

[0062] Add 1 g of the above tungsten disulfide to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake it thoroughly to disperse the tungsten disulfide powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and use an emulsifier to shear at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a tungsten disulfide dispersion with a tungsten disulfide concentration of 100 mg / mL.

[0063] Example 5

[0064] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0065] Add 2 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 4 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 200 mg / mL.

[0066] Example 6

[0067] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0068] Add 0.5 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of chlorosulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 4 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 50 mg / mL.

[0069] Example 7

[0070] Molybdenum disulfide with a particle size of 10 μm is provided and dried for later use.

[0071] Add 0.1 g of the above-mentioned molybdenum disulfide to a reagent bottle containing 10 mL of methanesulfonic acid, and shake it thoroughly to evenly disperse the molybdenum disulfide. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 4 hours to obtain a molybdenum disulfide dispersion with a molybdenum disulfide concentration of 10 mg / mL.

[0072] Example 8

[0073] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0074] Add 2 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of fluorosulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 4 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 200 mg / mL.

[0075] Example 9

[0076] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0077] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0078] 0.03 mol of sodium chloride was added to the hexagonal boron nitride dispersion, and the mixture was stirred until the viscosity of the solution did not change significantly. The dispersion completed the gelation process and formed a hexagonal boron nitride dispersion colloid, which can be used for further processing. Before the addition of sodium chloride, the viscosity of the hexagonal boron nitride dispersion was 270 mPa·s. After the addition of sodium chloride and the viscosity was stabilized, the viscosity of the hexagonal boron nitride dispersion colloid was 1836 mPa·s.

[0079] Example 10

[0080] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0081] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0082] 0.1 mol of sodium chloride was added to the hexagonal boron nitride dispersion, and the mixture was stirred until the viscosity of the solution did not change significantly. The dispersion completed the gelation process and formed a colloid, which can be used for further processing. Before the addition of sodium chloride, the viscosity of the hexagonal boron nitride dispersion was 270 mPa·s. After the addition of sodium chloride and the viscosity was stable, the viscosity of the hexagonal boron nitride dispersion was 12347 mPa·s.

[0083] Embodiment 11

[0084] Provide flake graphite with a particle size of 20μm to 30μm, dry it for use.

[0085] Add 0.9 g of the above-mentioned flake graphite to a reagent bottle containing 10 mL of trifluoromethylsulfonic acid, and shake it thoroughly to make the flake graphite evenly dispersed. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours. The flake graphite becomes graphene after exfoliation, thereby obtaining a graphene dispersion with a graphene concentration of 90 mg / mL.

[0086] 200 mg of dried Kevlar fiber was added to the graphene dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 min to dissolve the Kevlar fiber, thereby obtaining a colloid composite of the Kevlar fiber and the graphene dispersion.

[0087] Take 300 μL of the above colloid and squeeze it into a water coagulation bath at a rate of 0.5 mL / min using a 21G needle. Use a hair dryer to collect and dry the fibers, and collect the finished products to obtain composite fibers. The diameter of the composite fibers is between 120 μm and 190 μm.

[0088] Example 12

[0089] Molybdenum disulfide with a particle size of 10 μm is provided and dried for later use.

[0090] Add 1 g of the above molybdenum disulfide to a reagent bottle containing 10 mL of trifluoromethylsulfonic acid, and shake thoroughly to evenly disperse the molybdenum disulfide powder. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 4 hours to obtain a molybdenum disulfide dispersion with a molybdenum disulfide concentration of 100 mg / mL.

[0091] 500 mg of dried Kevlar fiber was added to the molybdenum disulfide dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 min to dissolve the Kevlar fiber, thereby obtaining a colloid composite of the Kevlar fiber and the molybdenum disulfide dispersion.

[0092] Take 300 μL of the above colloid and squeeze it into a water coagulation bath at a rate of 0.5 mL / min using a 21G needle. Use a hair dryer to collect and dry the fibers, and collect the finished products to obtain composite fibers. The diameter of the composite fibers is between 120 μm and 190 μm.

[0093] Embodiment 13

[0094] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0095] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0096] 500 mg of dried Kevlar fiber was added to the hexagonal boron nitride dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 minutes to dissolve the Kevlar fiber, thereby obtaining a colloid composite of the Kevlar fiber and the hexagonal boron nitride dispersion.

[0097] Take 300 μL of the above colloid and squeeze it into a water coagulation bath at a rate of 0.5 mL / min using a 21G needle. Use a hair dryer to collect and dry the fibers, and collect the finished products to obtain composite fibers. The diameter of the composite fibers is between 100 μm and 150 μm.

[0098] Embodiment 14

[0099] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0100] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0101] 400 mg of dried nylon 66 fiber was added to the hexagonal boron nitride dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 minutes to dissolve the nylon 66 fiber, thereby obtaining a colloid composite of nylon 66 fiber and hexagonal boron nitride dispersion.

[0102] Take 300 μL of the above colloid and squeeze it into a water coagulation bath at a rate of 0.5 mL / min using a 21G needle. Use a hair dryer to collect and dry the fibers, and collect the finished products to obtain composite fibers. The diameter of the composite fibers is between 100 μm and 120 μm.

[0103] Embodiment 15

[0104] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0105] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0106] 500 mg of dried polyetheretherketone was added to the hexagonal boron nitride dispersion, and the mixture was stirred at a high speed of 9500 rpm for 30 min to dissolve the polyetheretherketone, thereby obtaining a colloid composite of the polyetheretherketone and the hexagonal boron nitride dispersion.

[0107] Take 300 μL of the above colloid and squeeze it into a water coagulation bath at a rate of 0.5 mL / min using a 21G needle. Use a hair dryer to collect and dry the fibers, and collect the finished products to obtain composite fibers. The diameter of the composite fibers is between 110 μm and 130 μm.

[0108] Example 16

[0109] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0110] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0111] 40 mg of dried Kevlar fiber was added to the hexagonal boron nitride dispersion, and the mixture was stirred at a high speed of 9500 rpm for 20 min to dissolve the Kevlar fiber, thereby obtaining a colloid composite of the Kevlar fiber and the hexagonal boron nitride dispersion.

[0112] Take 300 μL of the above colloid and drip it into the ethanol coagulation bath at a rate of 0.1 mL / min using a 25G needle. When there are sufficient microspheres in the solution, pick up the microspheres and wash them in sufficient deionized water.

[0113] The microspheres in the deionized water were fished out and placed on a silicon wafer substrate preheated to 140° C. for drying, and then dried in a vacuum drying oven at 65° C. to obtain composite microspheres with a diameter distribution of 20 μm to 40 μm.

[0114] Embodiment 17

[0115] Provide flake graphite with a particle size of 20μm to 30μm, dry it for use.

[0116] Add 0.9 g of the above-mentioned flake graphite to a reagent bottle containing 10 mL of trifluoromethylsulfonic acid, and shake it thoroughly to make the flake graphite evenly dispersed. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours. The flake graphite becomes graphene after exfoliation, thereby obtaining a graphene dispersion with a graphene concentration of 90 mg / mL.

[0117] 200 mg of dried Kevlar fiber was added to the graphene dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 min to dissolve the Kevlar fiber, thereby obtaining a colloid composite of the Kevlar fiber and the graphene dispersion.

[0118] Take the colloid, heat it to 90°C and keep it warm for 0.5 hours. In a fume hood, pour the warmed colloid and scrape it onto a 316 stainless steel substrate. A stainless steel wire rod with a diameter of 30 μm is used as the scraping tool. The scraping speed is 35 mm / s. The temperature of the 316 stainless steel substrate is 95°C.

[0119] After the coating is formed, a membrane material is formed, and the membrane material is quenched with acid and cured with deionized water, and then repeatedly washed with deionized water.

[0120] The film material is then collected and vacuum dried at 65° C. to obtain a graphene composite film.

[0121] Embodiment 18

[0122] A hexagonal boron nitride powder with a diameter of 30 μm is provided, and the hexagonal boron nitride powder is pulverized into a hexagonal boron nitride powder with a diameter of 1 to 5 μm by ball milling.

[0123] Add 1 g of crushed hexagonal boron nitride powder to a reagent bottle containing 10 mL of trifluoromethanesulfonic acid, and shake thoroughly to disperse the hexagonal boron nitride powder evenly. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 2 hours to obtain a hexagonal boron nitride dispersion with a hexagonal boron nitride concentration of 100 mg / mL.

[0124] 500 mg of dried Kevlar fiber was added to the hexagonal boron nitride dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 minutes to obtain a colloid composite of the Kevlar fiber and the hexagonal boron nitride dispersion.

[0125] Take the colloid, heat it to 90°C and keep it warm for 0.5 hours. In a fume hood, pour the warmed colloid and scrape it onto a 316 stainless steel substrate. A stainless steel wire rod with a diameter of 30 μm is used as the scraping tool. The scraping speed is 35 mm / s. The temperature of the 316 stainless steel substrate is 95°C.

[0126] After the coating is formed, a membrane material is formed, and the membrane material is quenched with acid and cured with deionized water, and then repeatedly washed with deionized water.

[0127] The film material is then collected and vacuum dried at 65° C. to obtain a boron nitride composite film.

[0128] Embodiment 19

[0129] Molybdenum disulfide with a particle size of 10 μm is provided and dried for later use.

[0130] Add 1 g of the above-mentioned molybdenum disulfide to a reagent bottle containing 10 mL of trifluoromethylsulfonic acid, and shake it thoroughly to evenly disperse the molybdenum disulfide. Then place the reagent bottle on a Peltier refrigeration table, set the temperature to 0°C, and shear with an emulsifier at a shear rate of 20,000 rpm. The shearing process lasts for 4 hours to obtain a molybdenum disulfide dispersion with a molybdenum disulfide concentration of 100 mg / mL.

[0131] 500 mg of dried Kevlar fiber was added to the molybdenum disulfide dispersion, and the mixture was stirred at a high speed of 9500 rpm for 40 min to dissolve the Kevlar fiber, thereby obtaining a colloid composite of the Kevlar fiber and the molybdenum disulfide dispersion.

[0132] Take the colloid, heat it to 90°C and keep it warm for 0.5 hours. In a fume hood, pour the warmed colloid and scrape it onto a 316 stainless steel substrate. A stainless steel wire rod with a diameter of 30 μm is used as the scraping tool. The scraping speed is 35 mm / s. The temperature of the 316 stainless steel substrate is 95°C.

[0133] After the coating is formed, a membrane material is formed, and the membrane material is quenched with acid and cured with deionized water, and then repeatedly washed with deionized water.

[0134] The film material is then collected and vacuum dried at 65° C. to obtain a molybdenum disulfide composite film.

[0135] Comparative Example 1

[0136] The difference between Comparative Example 1 and Example 1 is that trifluoromethanesulfonic acid is replaced by water, and the remaining steps are the same as Example 1.

[0137] Comparative Example 2

[0138] The difference between Comparative Example 2 and Example 3 is that trifluoromethanesulfonic acid is replaced by water, and the remaining steps are the same as Example 3.

[0139] See also Figure 1A to Figure 7 , Figure 1A This is a scanning electron microscope image of hexagonal boron nitride before shearing in Example 1 of the present application. Figure 1B This is a scanning electron microscope image of hexagonal boron nitride in the hexagonal boron nitride dispersion prepared in Example 1 of the present application. Figure 1A and Figure 1B It can be seen that the preparation method of the present application achieves effective exfoliation and dispersion of hexagonal boron nitride.

[0140] Figure 2A This is a transmission electron microscope image of the graphene dispersion in Example 2 of the present application, Figure 2BThis is a transmission electron micrograph of the molybdenum disulfide dispersion in Example 3 of the present application. It can be seen that the preparation method of the present application achieves effective exfoliation and dispersion of flake graphite and molybdenum disulfide.

[0141] Figure 3 This is a physical picture of the hexagonal boron nitride dispersion with a concentration of 100 mg / mL prepared in Example 1 of the present application. Figure 4 This is a physical picture of the hexagonal boron nitride dispersed colloid prepared in Example 9 of the present application. Figure 4 It can be seen that the two-dimensional material dispersion provided in the present application can achieve a wide range of viscosity adjustment to adapt to different application environments.

[0142] Figure 5 From left to right in the figure are the graphene composite fiber prepared in Example 11, the molybdenum disulfide composite fiber prepared in Example 12, and the hexagonal boron nitride composite fiber prepared in Example 13.

[0143] Figure 6 This is a physical picture of the composite microspheres prepared using hexagonal boron nitride dispersion and Kevlar fiber in Example 16. It can be seen that the two-dimensional material dispersion prepared in this application can be processed into the form of composite microspheres to adapt to different application environments.

[0144] Figure 7 From left to right in the figure are the graphene composite film prepared in Example 17, the boron nitride composite film prepared in Example 18, and the molybdenum disulfide composite film prepared in Example 19.

[0145] The stripping efficiency of Examples 1-4 was tested. The stripping efficiency test method was as follows: 1 mL of the prepared two-dimensional material dispersion was injected into 200 mL of deionized water to dilute the acid therein, and the mixture was continuously stirred for 20 min with a magnetic stirrer at a stirring speed of 500 rpm; the mixture was washed with excess deionized water 5 times until the pH was 7, and the mixture was diluted to a 0.5 mg / mL two-dimensional material aqueous dispersion, and the dispersion was centrifuged at 3500 rpm for 30 min, the supernatant was taken and dried, and a well-stripped two-dimensional material was obtained. In general, it is generally recognized that the two-dimensional material in the supernatant has the best stripping effect, and the stripping efficiency is the mass of the two-dimensional material in the supernatant divided by the total mass of the two-dimensional material in 1 mL of the prepared two-dimensional material dispersion.

[0146] The stripping efficiencies of Examples 1-4 were tested respectively and the stripping efficiencies at different stripping times were recorded. The results are shown in Table 1.

[0147] Table 1.

[0148]

[0149] The present application also measured the stripping efficiency of Comparative Example 1 and Comparative Example 2 when the stripping time was 4 hours according to the above-mentioned stripping efficiency test method, which were 5.2% and 7.0%, respectively. It can be seen from the various embodiments and Table 1 that the present application can disperse the two-dimensional material at a high concentration using a specific superacid dispersion and can effectively improve the stripping efficiency of the two-dimensional material. As the stripping time increases, the stripping efficiency will gradually reach the optimal value and tend to be stable.

[0150] The throughput of Examples 1-4 and Comparative Examples 1-2 was calculated respectively. In this application, "throughput" refers to the output concentration per unit time. The throughput was calculated as the two-dimensional material stripping efficiency corresponding to a shearing time of 4 hours × the concentration of the two-dimensional material dispersion / shearing time. According to the throughput calculation formula, the throughput of the preparation method of Example 1 was 19.30 mg·mL -1 h -1 The throughput of the preparation method in Example 2 is 8.63 mg·mL -1 h -1 The throughput of the preparation method in Example 3 is 5.98 mg·mL -1 h -1 The throughput of the preparation method of Example 4 is 3.06 mg·mL -1 h -1 The throughput of the preparation method of Comparative Example 1 is 1.3 mg·mL -1 h -1 The throughput of the preparation method of Comparative Example 2 is 1.75 mg·mL -1 h -1 It can be seen that the preparation method of the two-dimensional dispersion provided in the present application is characterized by high throughput.

[0151] In summary, the present application uses a superacid with a Hammett acidity of less than -1 as a dispersion liquid for two-dimensional materials. The acid can be used to protonate the material to assist in dispersing and dissolving the two-dimensional material, thereby achieving high-concentration dispersion and high-throughput effects. The prepared two-dimensional material dispersion liquid can be directly used to prepare related composite materials, such as colloids, fibers, membranes, microspheres, etc., demonstrating the obvious advantages of the two-dimensional material dispersion liquid provided by the present application in dispersing two-dimensional materials and further processing.

[0152] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A two-dimensional material dispersion, characterized in that: include: A two-dimensional material and a dispersant, wherein the dispersant is a superacid with a Hammett acidity of less than -1.

2. The two-dimensional material dispersion according to claim 1, characterized in that: The dispersant includes at least one of trifluoromethanesulfonic acid, oleum, chlorosulfonic acid, methanesulfonic acid or fluorosulfonic acid.

3. The two-dimensional material dispersion according to claim 1, characterized in that: The two-dimensional material includes one or more of hexagonal boron nitride, graphene, molybdenum disulfide or tungsten disulfide.

4. The two-dimensional material dispersion according to claim 1, characterized in that: The concentration of the two-dimensional material in the two-dimensional material dispersion is 1 mg / mL to 200 mg / mL.

5. A method for preparing a two-dimensional material dispersion according to any one of claims 1 to 4, characterized in that: The following steps are involved: Providing a dispersant, wherein the dispersant is a superacid having a Hammett acidity of less than -1; The two-dimensional material and the dispersant are mixed, and then sheared and peeled to obtain a two-dimensional material dispersion.

6. The method for preparing a two-dimensional material dispersion according to claim 5, characterized in that: The shearing rotation speed is 7000 rpm to 30000 rpm, and the shearing time is 1 h to 4 h.

7. Use of the two-dimensional material dispersion according to any one of claims 1 to 4 in the preparation of composite fibers.

8. Use of the two-dimensional material dispersion according to any one of claims 1 to 4 in preparing composite microspheres.

9. Use of the two-dimensional material dispersion according to any one of claims 1 to 4 in preparing a composite film.

10. Use of the two-dimensional material dispersion according to any one of claims 1 to 4 in preparing a colloid.